Digitalisasi Pelaporan Bulan Dana PMI Kabupaten Jombang melalui Sistem Informasi Berbasis Web - Fajar Indra Kurniawan; Luki Ardiantoro (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2026)
The Indonesian Red Cross (PMI) of Jombang Regency carries out the Bulan Dana program as a humanitarian fundraising effort to support various social, health, and disaster-response activities. However, the reporting process for fundraising results from 21 subdistricts is still conducted manually using Excel spreadsheets sent via email or instant messaging applications. This condition causes several problems, including slow report recapitulation, low data accuracy, the absence of automatic validation, and limited reporting transparency. This community service program aims to digitalize the reporting system of Bulan Dana PMI Jombang through the development of a web-based information system. The implementation method was carried out participatively through the stages of socialization, training, technology implementation, mentoring, evaluation, and program sustainability. The developed system provides centralized data input, automatic validation, real-time dashboards, and digital report export features. The expected outcomes of this implementation are improved reporting efficiency, reduced input errors, increased information transparency for management and the public, and enhanced digital capacity of PMI staff in independently managing the system. Therefore, the digitalization of Bulan Dana reporting is expected to become a strategic solution for strengthening the accountability and professionalism of PMI Jombang Regency.